Analysis and estimation of the sediment yield of Pagsanjan-Lumban watershed in the Laguna De Bay basin using the Modified Universal Soil Loss Equation (MUSLE) - De Leon, Azel Lai D.; Herrera, Eugene C. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
River sediment discharge is one of the major problems affecting the country's largest freshwater lake, the the Laguna de Bay, primarily because of its effect on the lake's storage capacity, its impacts on water quality, and corresponding circulation. The Pagsanjan-Lumban watershed contributes the largest freshwater flow into the lake of about 18-20% of total flow (Hernandez, et.al, 2011) and is highly possible to contribute significant amounts of sediments to the lake. In this study, the Soil and Water Assessment Tool (SWAT) which utilizes the Modified Universal Soil Loss Equation (MUSLE) was used to predict the streamflow and suspended sediment yield of the Pagsanjan-Lumban watershed, Watershed information on rainfall, evaporation, topography, land- and soil- cover were accordingly analyzed and used to properly setup Pagsanjan-Lumban's hydrologic modeL After calibration and parameterization, good agreement between measured and simulated streamflow was indicated by a relatively high coefficient of determination (R2) of 0.88 and Nash Sutcliffe coefficient of 0.84. The calibrated parameters for discharge were then used to estimate the average monthly suspended sediment yield where another round of calibration was done. Observed values of suspended sediment ranges from 0.005 grams to 0.045 grams while simulated values ranges from 0.001 to about 0.05 grams. Further validation was then accomplished by comparing the annual sediment load to bathymetric changes in the lake adjacent to Pagsanjan-Lumban river mouth for 45 years (1963-2008). The sediment discharge rate from the model was found to be 446453.5046 tons/yr and is within acceptable range (1xI05) to the computed sediment rate using information which was at 532664.4371 tons/yr. While the simulation results are subject to further validation whenever more detailed and continuous information become available, it can be concluded that the MUSLE as utilized by the SWAT tool can be utilized for better watershed management planning. The calibrated watershed model was used to run two scenarios, one for assessing the effects of land cover changes, and the other one rainfall variability. Results showed that land conversion from forest and grasslands to agricultural lands by 26% increased the average annual streamflow and sediment yield by 36.4% and 79.3% respectively. Effect of a rainfall extreme was also assessed by simulating the 2009 wet year (typhoon Ketsana year) into the calibrated model. With the climate change scenario in rainfall, the streamflow and sediment yield increased by about 424 % and 258 % respectively. The study proved that land conversions greatly affect the sediment loading. The adverse effects of forests conversions show alarming results especially when it comes to streamflow and sediment yield. It is imperative that the consequences of these conversions be imparted and efforts should be exerted to address agricultural land conversions. The use of prediction models to estimate and assess suspended sediment characteristics was also shown to be a great aid in better watershed management planning especially since soil erosion, sediment transport and deposition is highly variable in space and time and monitoring is complex and expensive.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: River sediments; Reservoir sedimentation; Laguna de Bay Watershed (Philippines).